1H CSA parameters by ultrafast MAS NMR: measurement and applications to structure refinement - Miah, Habeeba K.; Cresswell, Rosalie; Iuga, Dinu; Titman, Jeremy J. (Elsevier, 2017)
A 1H anisotropic-isotropic chemical shift correlation experiment which employs symmetry-based recoupling sequences to reintroduce the chemical shift anisotropy in ν1 and ultrafast MAS to resolve 1H sites in ν2 is described. This experiment is used to measure 1H shift parameters for L-ascorbic acid, a compound with a relatively complex hydrogen-bonding network in the solid. The 1H CSAs of hydrogen-bonded sites with resolved isotropic shifts can be extracted directly from the recoupled lineshapes. In combination with DFT calculations, hydrogen positions in crystal structures obtained from X-ray and neutron diffraction are refined by comparison with simulations of the full two-dimensional NMR spectrum. The improved resolution afforded by the second dimension allows even unresolved hydrogen-bonded sites 1H to be assigned and their shift parameters to be obtained.